Control method for determining feasible pre-stresses of cable-struts structure. (May 2022) - Zhao, Yu; Guo, Jiamin; Jiang, Zhiyu; Chen, Weigang; Zhou, Guangen
Abstract: The structural stiffness of a cable-struts structure is dependent on its feasible pre-stresses. The search for the pre-stresses is an inverse problem, and classical approaches for this problem include the singular value decomposition (SVD) method. Driven by the need for more efficient methods, this study proposes a control method to search for feasible pre-stresses of cable-struts structures. First, we formulate the governing equation for cable-struts structures under pre-stresses and external loads. Then, we apply feedback control and use a proportional–integral–derivative (PID) controller to solve for the feasible pre-stresses based on the condition of zero structural displacements. To verify the proposed method, the study selects a Geiger dome, a Kiewitt dome and a honeycomb-type cable dome under three different loading conditions, and compares the present results against those from literature. The comparison shows that the developed control method can efficiently and accurately determine the feasible pre-stresses under external loads. The relative errors in the pre-stresses determined using the PID controller and using another two methods (singular value decomposition and iterative method) are less than 0.020% and 0.015% for the Geiger dome and the honeycomb-type dome, respectively. This study contributes to developing efficient methods for design of cable-struts structures under complex service loads. Highlights: This study formulates the governing equation for cable-struts structures under pre-stresses and external loads. This study proposes a PID-based control method to search for feasible pre-stresses of cable-struts structures. The PID controller can efficiently and accurately determine the feasible pre-stresses under external loads. This study provides a first attempt to apply control methods to the pre-stresses determination.